Defining Social Inclusion for People with Disabilities in Governance: Scoping and Thematic Literature Review - Nurhaeni, Ismi Dwi Astuti; Wiratama, Prama; Putri, Intan Sani; Nurdin, Asbiyal; Mulyadi, Asal Wahyuni Erlin; Haryani, Tiyas Nur; Sudibyo, Desiderius Priyo (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2023)
Consensus on a precise definition of social inclusion for people with disabilities remains elusive. This study aims to systematically review the definition of Social Inclusion for People with Disabilities in Governance (SIPDG) based on the related literature and offer basic theoretical insight into what might be considered relevant for establishing a definition of SIPDG. A scoping review was conducted with a qualitative synthesis of literature from SCOPUS. Articles were identified by final keywords of "social inclusion" AND “disability”*. The search produced 8,305 articles, of which 149 articles were included in the scoping review. A coding method was applied in the thematic analysis to identify recurring themes in the definition of SIPDG and generated five key themes delineating SIPDG. These cover the responsible subjects for social inclusion, People with Disabilities (PwD), barriers, disadvantaged areas, and social inclusion measures. The results of this study define SIPDG as an effort made by parties (government institutions, non-government organizations, the community, and PwD themselves) to optimize the existing potential of PwD (physical, intellectual, sensory, and mental disabilities) by eliminating obstacles (economic, structural, cultural, and personal) in various fields (public services, legislation, natural resources, economy, and technology) through the preparation and enactment of regulations, service delivery, provision of infrastructure, participation, and changes in community culture. Future research is expected to map the operational definition of SIPDG.